The MyD88 Pathway in Plasmacytoid and CD4+ Dendritic Cells Primarily Triggers Type I IFN Production against Measles Virus in a Mouse Infection Model - Takaki, Hiromi; Takeda, Makoto; Tahara, Maino; Shingai, Masashi; Oshiumi, Hiroyuki; Matsumoto, Misako; Seya, Tsukasa (The Journal of immunology (1950), 2013)
Infection by measles virus (MV) induces type I IFN via the retinoic acid–inducible gene I/melanoma differentiation–associated gene 5/mitochondrial antiviral signaling protein (MAVS) pathway in human cells. However, the in vivo role of the MAVS pathway in host defense against MV infection remains undetermined. CD150 transgenic (Tg) mice, which express human CD150, an entry receptor for MV, with the disrupting IFNR gene (Ifnar−/−), are susceptible to MV and serve as a model for MV infection. In this study, we generated CD150Tg/Mavs−/− mice and examined MV permissiveness compared with that in CD150Tg/Ifnar−/− mice. MV replicated mostly in the spleen of i.p.-infected CD150Tg/Ifnar−/− mice. Strikingly, CD150Tg/Mavs−/− mice were not permissive to MV in vivo because of substantial type I IFN induction. MV barely replicated in any other organs tested. When T cells, B cells, and dendritic cells (DCs) isolated from CD150Tg/Mavs−/− splenocytes were cultured with MV in vitro, only the DCs produced type I IFN. In vitro infection analysis using CD150Tg/Mavs−/− DC subsets revealed that CD4+ and plasmacytoid DCs, but not CD8α+ and CD8α−CD4− double negative DCs, were exclusively involved in type I IFN production in response to MV infection. Because CD150Tg/Mavs−/− mice turned permissive to MV by anti-IFNAR Ab, type I IFN produced by CD4+ DCs and plasmacytoid DCs plays a critical role in antiviral protection for neighboring cells expressing IFNAR. Induction of type I IFN in these DC subsets was abolished by the MyD88 inhibitory peptide. Thus, production of type I IFN occurs via the MyD88-dependent and MAVS-independent signaling pathway during MV infection.